Forbidden Memories Women's Experiences of 1965 in Eastern Indonesia - Kolimon, Mery; Wetangterah, Liliya (Monash University Publishing, 2015)
This is the first book to consider the experiences of women survivors of the 1965 anti-communist violence in the majority Christian region of Eastern Indonesia. So far, most studies of the 1965 violence have focused on the Muslim majority population of Java and the Hindu majority population of Bali. Forbidden Memories presents stories from across the regions of Sumba, Sabu, Alor, Kupang and other parts of West Timor of women who were imprisoned and tortured or whose husbands were murdered. The book comprises a critical examination of the role of the Protestant Church at the time of the violence and, in its aftermath, the ongoing sanctions and political purges against those considered to be supporters of the Indonesian Communist Party. The writers argue that religious and state institutions failed to care for this vulnerable community in the face of state terrorism and a culture of fear.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Political Science / Genocide & War Crimes; Political science; Electronic books